1985
DOI: 10.3354/meps023301
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins in aquatic fauna: a comprehensive review

Abstract: The presence and role of prostaglandin moieties in aquatic fauna have been a subject of study for only the last 15 yr. This review discusses the occurrence and physiological functions of these autocoids in a broad range of marine and freshwater fauna. The role of prostaglandins of the E and A series, in particular, in osmoregulation and mineral transport has been studied in several marine invertebrate phyla demonstrating analogy to the roles of these compounds in renal hemodynamics, diuresis, and electrolyte b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 22 publications
(53 reference statements)
0
6
0
1
Order By: Relevance
“…Fatty acid analyses of many molluscs (Joseph 1982(Joseph , 1989Napolitano et al 1988a) have shown that AA is selectively accumulated in phospholipids, indicating a specific role in cellular membranes. Arachidonic acid is also a precursor of prostaglandins and other eicosanoids (Ruggeri and Thoroughgood 1985), but there is no evidence conclusively showing that AA is an essential fatty acid in marine invertebrates.…”
Section: Bivalve Larvaementioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acid analyses of many molluscs (Joseph 1982(Joseph , 1989Napolitano et al 1988a) have shown that AA is selectively accumulated in phospholipids, indicating a specific role in cellular membranes. Arachidonic acid is also a precursor of prostaglandins and other eicosanoids (Ruggeri and Thoroughgood 1985), but there is no evidence conclusively showing that AA is an essential fatty acid in marine invertebrates.…”
Section: Bivalve Larvaementioning
confidence: 99%
“…Most recent attention has been given to essential fatty acid requirements of marine animals, focusing on the w3 or linolenic family of fatty acids, primarily 2 0 5~3 (eicosapentaenoic acid or EPA) and 22:6w3 (docosahexaenoic acid or DHA) (Cowey et al 1976;Waldock and Holland 1984). However, comparative studies have shown biosynthesis and activity of the eicosanoids (oxygenated and biologically active products of C20 fatty acids known in higher animals (Marcus 1984)) derived from both the w3 and w6 series of fatty acids in economically important bivalve molluscs and in other marine invertebrates (Christ and Van Dorp 1972;Nomura and Ogata 1976;Ruggeri and Thoroughgood 1985).…”
mentioning
confidence: 99%
“…The synthesis and inactivation pathways of PG have been studied extensively in higher-order mammals but are still limited in low-order nonmammalian or invertebrate animals, such as crustaceans. In aquatic animals, studies regarding the function of PGs are mainly focused on ovarian development [60,61]. With its collective findings, this study provides new insights into the synthesis and inactivation pathway of prostaglandins in crustaceans and may contribute to their regulatory mechanism in development and reproduction; nevertheless, further studies need to be conducted to understand the functions and regulatory mechanism of these key genes and PGs in crustaceans in depth.…”
Section: Discussionmentioning
confidence: 94%
“…It may be related to the unexpectedly low levels of 20:5(n-3) in the CORN diet, which resulted in lower circulating levels of this FA, and perhaps less competition among these two C 20 PUFAs for eicosanoid synthesis. Given the vasoactive and osmoregulatory effects of eicosanoids derived from 20:4(n-6) in aquatic animals (reviewed by Ruggeri and Thoroughgood 1985), the rapid decline in 20:4(n-6) in the CORN group following the stressor exposure may be related to the elevated plasma osmolality levels observed in these fish.…”
Section: Discussionmentioning
confidence: 99%